2012
DOI: 10.15517/rbt.v60i1.2766
|View full text |Cite
|
Sign up to set email alerts
|

Composición taxonómica y aspectos zoogeográficos de peces de profundidad (90-540m) del Golfo de California, México.

Abstract: Taxonomic composition and zoogeographical aspects of deep sea fishes (90-540m) from the Gulf of California, Mexico. The Gulf of California has a high variety of ecosystems that allow different services and the fishery resources play a prominent role in its ecology, evolution and economics. Fish coastal species have been previously reported for most coastal areas, especially those species that are subject to fishing, however, little is known on the species from deep sea zones, due to sampling difficulties. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Garman (1899: 51), Poss (1995Poss ( : 1547, Bussing & López (1994: 82;2009: 452), Bearez (1996: 735), Moser (1996c: 738), Grove & Lavenberg (1997: 295), Chirichigno & Vélez (1998: 272), : 1773, Imamura (2009: 240), López-Martínez et al (2012: 352), Del Moral-Flores et al (2013, Gómez et al (2014: 394) and Robertson & Allen (2015: 1007. (79) Pontinus sierra .…”
Section: Merlucciidaementioning
confidence: 99%
See 1 more Smart Citation
“…Garman (1899: 51), Poss (1995Poss ( : 1547, Bussing & López (1994: 82;2009: 452), Bearez (1996: 735), Moser (1996c: 738), Grove & Lavenberg (1997: 295), Chirichigno & Vélez (1998: 272), : 1773, Imamura (2009: 240), López-Martínez et al (2012: 352), Del Moral-Flores et al (2013, Gómez et al (2014: 394) and Robertson & Allen (2015: 1007. (79) Pontinus sierra .…”
Section: Merlucciidaementioning
confidence: 99%
“…Literature. Gilbert & Starks (1904: 165), Böhlke (1953: 125), Pequeño (1989: 57), Miller & Richards (1991b: 760), Castro-Aguirre et al (1993: 88), Bussing & López (1994: 86;2009: 453), Balart et al (1995: 82), Bussing (1995Bussing ( : 1645, Bearez (1996: 735), Richards (1996: 797), De La Cruz Agüero et al (1997, Chirichigno & Vélez (1998: 265), Castro-Aguirre et al (1999: 246), Lucano-Ramírez et al (2005: 1), Raymundo-Huizar et al (2008: 7), : 1773, López-Martínez et al (2012: 352), Del Moral-Flores et al (2013, Murase et al (2014Murase et al ( : 1405, Fuentes et al (2015: 615) and Robertson & Allen (2015: 1058.…”
Section: Merlucciidaementioning
confidence: 99%
“…Sex distribution showed greater proportion of females in a depth range from 170 to 230 m and of males from 230 to 270 m. The majority of the females were from maturity stage III to V (82%); 98% of the males were from stages I to III. (López-Martínez et al, 2012;Rábago-Quiroz et al, 2015). The greater abundances could be related to migratory habits from deeper to shallower waters for reproductive purposes (Rábago-Quiroz et al, 2015), which explains the greater proportion of mature females and at greater depths than males.…”
mentioning
confidence: 99%
“…The Peruvian flounder Etropus peruvianus (Paralichthyidae) occurs in the East Pacific, from Baja California to Perú, including the Gulf of California ( Van der Heiden, 2010;López-Martínez et al, 2012;Del MoralFlores et al, 2013), where it is identified as a component of the Sinuscalifornian, Mexican, and Panamic provinces. The Peruvian flounder ranges at depths of 46 to 125 m in benthic habitats close to sandy and muddy bottoms, including rubble, its maximum size is 100 mm in total length (Hensley, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation